2023
DOI: 10.3389/fphys.2023.1114488
|View full text |Cite
|
Sign up to set email alerts
|

Chronic larval exposure to thiacloprid impairs honeybee antennal selectivity, learning and memory performances

Abstract: The use of agricultural neonicotinoid insecticides has sub-lethal chronic effects on bees that are more prevalent than acute toxicity. Among these insecticides, thiacloprid, a commonly used compound with low toxicity, has attracted significant attention due to its potential impact on the olfactory and learning abilities of honeybees. The effect of sub-lethal larval exposure to thiacloprid on the antennal activity of adult honeybees (Apis mellifera L.) is not yet fully understood. To address this knowledge gap,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 90 publications
2
6
1
Order By: Relevance
“…We showed that chronic larval exposure to thiacloprid impaired honey bee response to sucrose in emerged bees along with olfactory associative learning and memory performance. The results are consistent with previous research that indicated thiacloprid adversely affected honey bee cognitive performance [ 17 , 24 ]. Sucrose sensitivity was used as an important indicator of foraging efficiency.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We showed that chronic larval exposure to thiacloprid impaired honey bee response to sucrose in emerged bees along with olfactory associative learning and memory performance. The results are consistent with previous research that indicated thiacloprid adversely affected honey bee cognitive performance [ 17 , 24 ]. Sucrose sensitivity was used as an important indicator of foraging efficiency.…”
Section: Discussionsupporting
confidence: 93%
“…Similar adverse effects on learning and memory have been mentioned in previous research on adult bees (honey bee or stingless bees) exposed to thiacloprid [11,16,24]. Furthermore, these findings demonstrated that despite surviving to adulthood, honey bee larvae exposed to thiacloprid experience cognitive disorders after emerging, which aligns with the impaired olfactory associative behavior identified in honey bees exposed to imidacloprid or thiacloprid [17].…”
Section: Thiacloprid Impaired Honey Bee Learning and Memory Abilitysupporting
confidence: 85%
See 2 more Smart Citations
“…In agroecosystems, honey bees are also likely to be exposed to numerous agrochemicals, including insecticides, herbicides, and fungicides (Mullin et al, 2010;Johnson, 2015). Accumulated studies have provided insights into the acute toxicity and sublethal impacts of xenobiotic exposure on bees' foraging, learning, memory, gut microbiota, and immunity (El Hassani et al, 2005Yang et al, 2008;Hladun et al, 2012;Williamson et al, 2014;Balbuena et al, 2015;Wright et al, 2015;Di et al, 2016;Motta et al, 2018;DesJardins et al, 2021;Kadlikova et al, 2021;Ke et al, 2023). Interestingly, when present at low concentrations, certain xenobiotics have been found to exhibit hormetic effects that can benefit honey bee health (Köhler et al, 2012;Wright et al, 2013;Cutler et al, 2022).…”
Section: Introductionmentioning
confidence: 99%